From the noun phrase to the determinative phrase - Esquivel Villafana, Jorge (2002)
In the development of modern linguistics, it is evident the extraordinary relevance that the lexical category determiner has experienced to the detriment of the other constituents of the FN in the consideration of its hierarchical status, since it has gone from being a non-nuclear element (optional or obligatory) in the nominal structuring in generative grammar (according to Chomsky, Postal, Fillmore, etc.) to a nuclear position, generator of its own maximum projection, the determinative phrase, in categorial grammar (according to Abney). Over the years, from 1957 to the present, its position has been consolidated, as reported by the various versions of FN that were configured with the support of the linguistic evidence of the moment. Hence our interest in examining its impressive evolution within the framework of the two modern currents: the generative and the categorial. The analysis of the versions of Chomsky, Postal, and Fillmore, and also that of Abney, as the most prominent representatives of both grammars, will allow us to know not only the theoretical motivations that supported the versions in question, but also the evolution and enrichment of the theoretical arguments in favor of Abney's proposal, which is assumed to be the most appropriate at present.